2018
DOI: 10.1039/c8cc01007b
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-driven switching of the Ullmann coupling on Au(111)

Abstract: We demonstrate a method to selectively switch the Ullmann coupling reaction of 2,8-dibromodibenzothiophene on a Au(111) support. The Ullmann coupling reaction is effective already at low temperature, but the complete inhibition of the same reaction can be achieved on Au(111) pre-exposed to H2S. The marked difference in reactivity of pretreated Au(111) is explained by the S-passivation of free Au atoms emerging from reconstruction sites. The inhibited state can be fully lifted by removing the S via hydrogen gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Figure a shows a typical STM image of isolated poly‐DBT nanowires, obtained after deposition of 2,8‐DBDBT onto a clean Au(111) surface held at 150 K and imaged at 110 K 32. Ullmann coupling reactions have been triggered even at this low temperature on Au(111), resulting in DBT molecules self‐assembled into a characteristic chain network (Figure 2b).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Figure a shows a typical STM image of isolated poly‐DBT nanowires, obtained after deposition of 2,8‐DBDBT onto a clean Au(111) surface held at 150 K and imaged at 110 K 32. Ullmann coupling reactions have been triggered even at this low temperature on Au(111), resulting in DBT molecules self‐assembled into a characteristic chain network (Figure 2b).…”
Section: Resultssupporting
confidence: 90%
“…A contributing factor to the low reactivity seen for the pristine sulfided samples is that Ullmann coupling itself seems to be inhibited by residual S on the Au terraces originating from the H 2 S dosed during MoS 2 synthesis. The mobile sulfur species are not imaged directly but the presence of residual sulfur on Au(111) terraces has in previous studies been shown to lead to inhibition of the Ullmann coupling, possibly due to S coordination and passivation of the Au atoms that can catalyze the Ullmann coupling 32. In our case, the presence of S on the surface can sometimes directly be evidenced by increasing the overage of 2,8‐DBDBT (reducing S mobility) where the S overlayers then become visible (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Also protective group strategies that are well established in solutionphasec hemistry have been developed. [30][31][32] In addition, additives have been used to supress acertain reaction [33,34] and preorganization by different self-assembled structures has been shownt oi nfluencet he reactivity. [35,36] Alternatively, one can run the process at different coverages [37][38][39] or temperatures [40] and use these readily varied reactionp arameters for product control.H owever, to date only few exampleso nr eactionc ontrol based on surfacec overage in two-dimensionalc hemistry have been reported.…”
Section: Introductionmentioning
confidence: 99%